2005
DOI: 10.1007/s10585-005-3098-x
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Mediates Transendothelial Migration in vitro by Ligating Endothelial Cell ICAM-1

Abstract: MUC1 is a transmembrane glycoprotein expressed by normal breast epithelium and virtually all breast cancers. MUC1 is normally restricted to the apical surface of epithelia and loss of this polarized distribution in breast carcinomas is associated with lymph node metastasis. Our previous work found that MUC1 can bind intercellular adhesion molecule-1 (ICAM-1), mediating adhesion of breast cancer cells to a simulated blood vessel wall, and also triggering a calcium-based signal in the MUC1-bearing cells. It is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 57 publications
3
95
3
1
Order By: Relevance
“…During metastasis, tumor cells lose their original tissue contacts, invade the extracellular matrix, transit via the lymphatic/blood system, and adhere to and then extravasate at the secondary metastatic site. Most recently, consistent with our previous transendothelial migration study (8), we found that MUC1, by ligating ICAM-1 on stromal fibroblasts, also potentiates cell invadopodial protrusions and stromal invasion (data not shown). This implies that tumor cells may use MUC1 (no siRNA) as a control, the expression levels of CrkL protein were significantly knocked down by CrkL siRNA (f50%) 24 h posttransfection in both T47D and 293T SYM25 cells, and the levels of CrkL were further reduced (f70%) after 48 h of transfection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…During metastasis, tumor cells lose their original tissue contacts, invade the extracellular matrix, transit via the lymphatic/blood system, and adhere to and then extravasate at the secondary metastatic site. Most recently, consistent with our previous transendothelial migration study (8), we found that MUC1, by ligating ICAM-1 on stromal fibroblasts, also potentiates cell invadopodial protrusions and stromal invasion (data not shown). This implies that tumor cells may use MUC1 (no siRNA) as a control, the expression levels of CrkL protein were significantly knocked down by CrkL siRNA (f50%) 24 h posttransfection in both T47D and 293T SYM25 cells, and the levels of CrkL were further reduced (f70%) after 48 h of transfection.…”
Section: Discussionsupporting
confidence: 92%
“…5,6), an adhesion molecule normally involved in the firm arrest and the subsequent extravasation of leukocytes through the vascular endothelium during inflammation (7). Analogous to the involvement of ICAM-1 in the extravasation of leukocytes, our recent transwell studies suggested that the MUC1/ICAM-1 interaction also facilitates in vitro transendothelial migration of MUC1-bearing cells through a monolayer of ICAM-1 -expressing cells (8). This is significant, as the adhesion of tumor cells to endothelium and the subsequent exit from vasculatures of secondary organs are thought to be critical steps in metastasis (9,10).…”
Section: Introductionmentioning
confidence: 95%
“…In fact, ÎČ2 integrin is expressed in melanoma, lymphoma, myeloma, gastrointestinal carcinomas, and was recently reported in breast cancer (29,(62)(63)(64)(65). Another ICAM-1 ligand, MUC-1, is expressed on breast cancer cells (23), as well as ovarian, prostate, gastric and pancreatic cancer cells and liver metastases (66). The hyaluronan receptor CD44 and its isoforms, which can be used alongside others markers for cancer stem cell identification (67), are expressed on breast, colorectal and pancreatic cancers cells (68)(69)(70).…”
Section: Tumor Cell Adhesion: Lending Tumor Cells a Handmentioning
confidence: 94%
“…Several adhesion molecules, such as E-selectin, vascular cellular adhesion molecule (VCAM)-1 and ICAM-1, exhibit increased expression in the liver during metastatic invasion (22). Among them, ICAM-1 mediates several stages of the metastatic cascade, including the adhesion of tumor cells to the endothelial wall (23)(24)(25), endothelial cell activation of pro-metastatic signaling pathways (26)(27)(28), tumor cell extravasation (23,29), the recruitment of immune cell populations (28,30,31), the pro-angiogenic response (32) and the transdifferentiation of stellate cells during the desmoplastic response (33,34). This review will focus on the role of ICAM-1 during the different events of the metastatic cascade that drives colonization of the liver by circulating tumor cells, and how it modulates the liver microenvironment to facilitate metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…These abnormal interactions trigger inappropriate activation of intracellular signalling pathways and thus promote the growth, proliferation, and survival of cancer cells. [6][7][8][9][10][11] Tecemotide (L-BLP25) is a MUC1 antigenspecifi c immunotherapy capable of inducing a T-cell response to MUC1 in both a preclinical MUC1-transgenic lung cancer mouse model 12 and in patients. [13][14][15] A National Cancer Institute (NCI) project to prioritise cancer antigens ranked MUC1 very highly on the basis of predefi ned criteria.…”
Section: Introductionmentioning
confidence: 99%